IMPLEMENTATION OF DIVERSION IN THE JUVENILE CRIMINAL JUSTICE SYSTEM IN SAMARINDA DISTRICT COURT - Rido, Muhammad; Rosifany, Ony; Imron (Awang Long Law Review, 2025)
Children need to be protected from the negative effects of rapid development, globalization in the information and communication industry, scientific and technological breakthroughs, and changes in lifestyle and lifestyle of some parents. These factors result in fundamental social changes and have a major impact on children's behavior and values. Children who commit crimes are greatly influenced by socialization, education, playmates, and other external factors. This study uses the normative legal research method, utilizing primary and secondary legal sources, especially those that provide fresh or current scientific data or alternative perspectives on established facts or ideas. These sources in this case are books, journals, theses or dissertations, and other legal papers.The results of this study are that the implementation of Diversion is one of the restorative justice approaches that can be used to handle juvenile crimes. By focusing on how to return to the original state, diversion through a restorative justice approach is a fair and reasonable solution to children's cases involving perpetrators of criminal acts, victims, families of criminals, and other parties who collectively seek a solution to the crime and its consequences for the victim. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System regulates the procedures for diversion. Various studies have shown that there are obstacles that hinder the implementation of effective diversion. One of the main challenges is the lack of in-depth understanding of the procedures and principles underlying diversion among law enforcement officers and the community.